Functional genetics of lung function associated gene GPR126 - Hall, Robert (2020)
GPR126 lies on chromosome 6q24 and variants in this region are reproducibly associated with lung function and COPD in genome wide association studies (GWAS).This association signal includes a non-synonymous single nucleotide polymorphism (SNP), rs17280293 (minor allele frequency = ~2.9%) which results in the amino acid substitution Ser123Gly within the GPR126 coding region. GPR126 is a G protein coupled receptor belonging to the adhesion family of receptors. The aim of the work described in this thesis was to define the role ofGPR126 in the human lung and in pulmonary disease. My specific aims were to i) identify the GPR126 expression profile in the lung and in airway structural cells ii) determine potential causal variants within the association signal iii) define the effects of missense variant Ser123Gly on GPR126 function iv) determine the function of GPR126 signalling in human airway structural cells.